Development of Learning Experience Based on STEAM Education through Cooking to Promote Computational Thinking in Early Childhood - Noinak, Wannisa; Onthani, Angkana (Journal of Buddhist Education and Research (JBER), 2025)
This research and development study aimed to develop and evaluate the effectiveness of STEAM Education-based learning experiences through cooking activities to promote computational thinking in early childhood students according to the 75/75 criterion, and to examine implementation results by comparing computational thinking before and after intervention and studying developmental progress during the learning process. The study involved 28 kindergarten 3/1 students in the second semester of academic year 2024 from Anuban Karoon Wat Trapangthong School, selected through simple random sampling using classroom as the sampling unit. Research instruments included STEAM Education learning experiences through cooking activities, computational thinking assessment rubrics during learning, and computational thinking tests, with data analyzed using percentages, means, standard deviations, One Group Pretest-Posttest Design, and dependent t-test. Findings revealed that the STEAM Education-based learning experience through cooking activities consisted of five steps: Menu Selection, Menu Analysis and Equipment Preparation Introduction, Cooking Implementation, Idea Exchange, and Evaluation and Improvement, with appropriateness of the learning experience at the highest level (M = 5.00, S.D. = 0.00), lesson plan appropriateness at the highest level (M = 4.79, S.D. = 0.19), and efficiency of 74.71/75.56, meeting the established criterion. Implementation results showed that students' post-intervention computational thinking scores were significantly higher than pre-intervention scores at the .05 statistical significance level, and students demonstrated notable computational thinking development during activities through improvement in key components including Decomposition (breaking large problems into smaller parts), Pattern Recognition, Abstraction (identifying essential information), and Algorithm Design (sequencing work steps). Students could systematically design and determine cooking procedures, predict outcomes of each step, and appropriately identify and correct errors during cooking activities, indicating that STEAM Education through cooking experiences effectively promoted computational thinking skills in early childhood education, enabling children to apply systematic problem-solving approaches in practical, engaging contexts that fostered deeper cognitive development and hands-on learning experiences.